Staging und Therapieansprechen mit radiologischen und nuklearmedizinischen Verfahren bei Non-Hodgkin-Lymphomen (NHL): Leitthema - Neelsen, Christian; Mohammad, Ahmad; Schlemmer, Heinz-Peter; Dimitrakopoulou-Strauss, Antonia; Sachpekidis, Christos (Die Radiologie, 2025)
Clinical/methodical issue Non-Hodgkin lymphomas (NHL) represent a heterogeneous group of malignant diseases in which the choice of imaging modality and response criteria strongly depends on histology and clinical context. Selecting the appropriate method is essential for individualized treatment planning. Standard radiological methods According to the Lugano classification, 18F‑fluorodeoxyglucose positron emission tomography/computed tomography (18F‑FDG PET/CT) is the reference standard for staging and response assessment in 18F-FDG-avid NHL. For other lymphoma subtypes with low or variable 18F-FDG avidity, or in cases where reimbursement by statutory health insurance (GKV) is lacking, contrast-enhanced CT is typically used. Methodological innovations This article discusses the new classification systems Lymphoma Response to Immunomodulatory Therapy Criteria (LYRIC) and Response Evaluation Criteria in Lymphoma (RECIL), as well as specific features of certain lymphoma subtypes and novel imaging approaches such as whole-body MRI and innovative PET tracers. Performance This narrative review does not include a systematic evaluation of sensitivity or specificity data. Achievements In 18F-FDG-avid lymphomas 18F‑FDG PET/CT remains the gold standard for precise staging and response assessment. Practical recommendations Imaging is essential for tailored therapy planning and monitoring in NHL. As most NHL subtypes are 18FDG-avid, PET/CT is the reference standard. However, contrast-enhanced CT continues to play a significant role, particularly in Germany. New PET tracers and whole-body MRI offer promising approaches but require further studies and standardization.